Therapeutic Studies and Post Therapeutic Follow-up Evaluation of Dogs Affected by Cerebral Babesiosis - Nagarjuna, Gollapalli; Reddy, Bhavanam Sudhakara; Saritha, Gungi; Sivajothi, Sirigireddy (International Journal of Bio-resource and Stress Management, 2026)
The present study was carried out from October, 2023 to September, 2024 at Department of Veterinary Medicine, College of Veterinary Science, Proddatur. The research study was carried out to investigate cerebral babesiosis in dogs to record the therapeutic response and post therapeutic assessment. The study was carried out on the dogs presented to the different veterinary polyclinics in YSR and Krishna districts of Andhra Pradesh. Confirmation of the babesiosis was done by microscopic examination of Giemsa-stained blood smears and further by polymerase chain reaction assay as detection of 670 bp amplicons specific to the Babesia gibsoni in blood. Based on the presence of the neurological signs, demonstration of Babesia organisms in red blood cells of cerebrospinal fluid, 8.08% (11/136) of dogs with babesiosis diagnosis had the cerebral babesiosis. Neurological symptoms observed in dogs with cerebral form included ataxia, stiffness of hind limbs, paddling, opisthotonus, twitching of hind limbs, seizures, head pressing, stupor, decerebrate rigidity, decerebellate rigidity, circling, nystagmus, blindness and paraplegia. Dogs were administered with deep intramuscular injection of diminazene aceturate, in two doses at 48-hour intervals at a dose of 3.5 mg kg-1 body weight, tablet doxycycline @ 5 mg kg-1 body weight every 12 hours PO, tablet enrofloxacin @ 10 mg kg-1 body weight every 24 hours PO, tablet metronidazole @ 15 mg kg-1 body weight BID, PO along with supportive and symptomatic therapy. Two of the eleven dogs in the study recovered after receiving appropriate standard therapy, according to a post-therapeutic assessment of dogs with cerebral babesiosis.